2015
DOI: 10.1002/prot.24954
|View full text |Cite
|
Sign up to set email alerts
|

Conformational fluctuations of the AXH monomer of Ataxin-1

Abstract: In this paper, we report the results of molecular dynamics simulations of AXH monomer of Ataxin-1. The AXH domain plays a crucial role in Ataxin-1 aggregation, which accompanies the initiation and progression of Spinocerebellar ataxia type 1. Our simulations involving both classical and replica exchange molecular dynamics, followed by principal component analysis of the trajectories obtained, reveal substantial conformational fluctuations of the protein structure, especially in the N-terminal region. We show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 42 publications
4
44
0
Order By: Relevance
“…Based on those findings, and in accordance with previous observations, it has been suggested that interactions leading to the dimer formation might be able to stabilize the Nter region of the AXH m , which is involved in the dimeric interface . However, several issues concerning the protein‐protein interactions characterizing AXH conformational stability and, more generally, a dynamic description of protein conformational changes at dimer interface, are still unknown.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…Based on those findings, and in accordance with previous observations, it has been suggested that interactions leading to the dimer formation might be able to stabilize the Nter region of the AXH m , which is involved in the dimeric interface . However, several issues concerning the protein‐protein interactions characterizing AXH conformational stability and, more generally, a dynamic description of protein conformational changes at dimer interface, are still unknown.…”
Section: Introductionsupporting
confidence: 80%
“…Recently, classical and biased molecular dynamics (MD) has been applied to investigate the extensive conformational fluctuation of the Nter tail of the AXH monomer (AXH m ) in solution . It has been demonstrated that AXH m is characterized by a relatively stable structure with, in general, highly conserved domains, except for the Nter tail switching between several conformations.…”
Section: Introductionmentioning
confidence: 99%
“…The JD residues mainly responsible for the interaction with TFE have been identified by contact probability plots [11]. The secondary structure of the protein has been calculated by the STRIDE software [54] on several snapshots along the simulation time at the conformational equilibrium, as done in previous studies [11,12,13,55,56]. Two descriptors were considered to identify the JD conformational properties: The JD Radius of Gyration (RG), and the hairpin angle, successfully employed in recent literature to describe the sampling of JD conformations [12,38].…”
Section: Methodsmentioning
confidence: 99%
“…The AXH domain is known as a dimerization domain and is the only globular dimer forming region identified in the protein [92]. Additionally, the AXH folds independently into an oligonucleotide-binding fold, able to recognise RNA with a similar nucleotide preference, to that of full length ataxin-1 [91,93]. Second to RNA binding, the AXH domain contains a cluster of charged surface residues that allows for another secondary binding surface.…”
Section: Wild-type and Mutant Proteinmentioning
confidence: 99%
“…This leads to the several protein-protein interactions through the ataxin-1 AXH domain, namely a paralog of ataxin-1, brother of ataxin-1 (BOAT), which also contains a AXH domain, the SMRT/SMRTER and Capicua proteins [94]. These interactions, along with interactions between several transcriptional factors, give ataxin-1 its transcriptional repression activity [90,91,93].…”
Section: Wild-type and Mutant Proteinmentioning
confidence: 99%